Entrepreneurial motivation: the impact of cultural capital on the 'who' is motivated. (9th July 2019) - Lloyd, Warren
Almost all definitions propose entrepreneurs as especially motivated and talented individuals. Therefore, understanding and explaining the psychological forces within the individual that motivates them is highly desired. This paper is intended to investigate studies on entrepreneurial motivation to identify an effective theory that enables recognising 'who' could potentially become an entrepreneur, rather than 'how' and 'why' individuals choose to become entrepreneurs. Of the theories discussed, McClelland's achievement need (n-ach) is accepted as the most apt in this review. It is further noted in this paper that in defining and explaining this need, and its influence on entrepreneurship, an understanding of the impact of an individual's culture, beliefs and attitudes, encompassed in their cultural capital, is required. Primarily by evaluation of literature in this report, strong evidence indicates and supports the distinctive impact of culture on entrepreneurial motivation. In conclusion, a framework is proposed for further study investigating the impact of cultural capital on n-ach in home and immigrant entrepreneur cultural groups.